RELOADING THE DRAGON LADY: READING THE CHARACTER OF CHUN LI IN STREET FIGHTER: THE LEGEND OF CHUN LI - Adelia, Silvy; Fitriana, Ephrilia; Andriani, Yeni; Kusumaningtyas, Dwi; Dirgantari, Alfi (English Review: Journal of English Education, 2024)
Street Fighter: The Legend of Chun Li movie revolves around the journey of Chun Li, a Chinese female fighter of the Street Fighter series, and her eventual fight against Bison. This study focuses on the portrayal of Chun Li as a representative of Asian women in an American movie, and compares it to her original portrayal in the game. There are two big groups of representation of Asian women in the Western media: the submissive ‘lotus blossom baby’ and the aggressive ‘dragon lady.’ As a form of content analysis, this study analyzes both textual and visual elements of the Street Fighter: The Legend of Chun Li movie and Street Fighter game series which represent the portrayal of an Asian woman character named Chun Li. Result shows that Chun Li character in the movie leans more towards the ‘dragon lady’ group with her strong and seductive characteristics, while her game self exhibits a broader range of qualities.